Pengaruh Inflasi dan Nilai Tukar Terhadap Indeks Harga Saham pada JII yang Dimoderasi oleh Harga Emas Dunia (Studi Kasus Sebelum dan Sesudah Covid 19 Periode 2018-2021) - Reina Tasha Baskara; Iiz Izmuddin; Siti Faizah; Habil Febrian; Mahdalena Daulay; Jaimanida Zai (ITB AAS INDONESIA Surakarta, 2023)
Abstract This study aims to determine the effect of inflation and exchange rates on the stock price index (JII) in Indonesia with world gold prices as a moderating variable. There is research data using time series data for the 2018-2019 period before Covid and the 2020-2021 period during the Covid period. Data analysis technique uses PLS (Partial Least Square) processing using Warp-PLS 8.0. The test results using the SEM-PLS approach show that in the pre-covid period, inflation had a negative and significant relationship to the JII Stock Price Index. Meanwhile, inflation has a negative and insignificant relationship to the JII Stock Price Index during the covid period. Meanwhile, the Exchange Rate had a negative and significant relationship to the JII Stock Price Index before covid. Similarly, during the covid period, the Exchange Rate had a negative and significant relationship to the JII Stock Price Index during the covid period. The World Gold Price proved unable to moderate the relationship between Inflation and the JII Stock Price Index before Covid and was able to moderate the relationship between Inflation and the JII Stock Price Index during the Covid period. World Gold Prices proved to be able to moderate the influence of the relationship between the Exchange Rate and the JII Stock Price Index before the covid and were unable to moderate the effect of the relationship between the Exchange Rate and the JII Stock Price Index during the covid period.